Diplomeroterpenoid G: An unusual meroterpenoid from Mimosa pudica Linn. (Mimosaceae). (28th April 2023) - Kenmogne, Claudie F.; Eckhardt, Paul; Tchuenguem, Roland T.; Groß, Jonathan; Ngouafong, Francis T.; Ponou, Beaudelaire K.; Dzoyem, Jean P.; Teponno, Rémy B.; Opatz, Till; Tapondjou, Léon A.
Graphical abstract: Abstract: An unusual meroterpenoid with a pyran ring (diplomeroterpenoid G) was isolated from the methanolic extract of the aerial part of Mimosa pudica together with fourteen known compounds: apigenin, tricin, quercetin, chryoeriol, 7, 4′-dihydroxylfavone, 5, 7, 2′, 5′-tetrahydroxyflavone, isoorientin, quercetin 3- O - β -d -xylopyranoside, quercetin 3-O- α -l -arabinofuranoside, quercetin 3- O - β -d -glucopyranoside, methylinositol, betulinic acid, oleanolic acid, and β -sitosterol 3- O - β -d -glucopyranoside. Their structures were elucidated by a careful analysis of the spectroscopic data (UV, IR, 1D and 2D NMR), high resolution mass spectrometry, electronic circular dichroism, DFT calculations, and by comparison of their data with those reported in the literature. The antibacterial potential of the methanolic extract and some of the isolated compounds were evaluated on five strains of bacteria. Compound 6 showed the most potent antibacterial activity against Proteus mirabilis (MIC = 32 µg/mL).